Inferring the Significance of the Polyamine Metabolism in the Phytopathogenic Bacteria Pseudomonas syringae: A Meta-Analysis Approach - Solmi, Leandro; Rosli, Hernán G.; Pombo, Marina A.; Stalder, Santiago; Rossi, Franco R.; Romero, Fernando M.; Ruiz, Oscar A.; Gárriz, Andrés (Frontiers in Microbiology, 2022)
To succeed in plant invasion, phytopathogenic bacteria rely on virulence mechanisms to subvert plant immunity and create favorable conditions for growth. This process requires a precise regulation in the production of important proteins and metabolites. Among them, the family of compounds known as polyamines have attracted considerable attention as they are involved in important cellular processes, but it is not known yet how phytopathogenic bacteria regulate polyamine homeostasis in the plant environment. In the present study, we performed a meta-analysis of publicly available transcriptomic data from experiments conducted on bacteria to begin delving into this topic and better understand the regulation of polyamine metabolism and its links to pathogenicity. We focused our research on Pseudomonas syringae, an important phytopathogen that causes disease in many economically valuable plant species. Our analysis discovered that polyamine synthesis, as well as general gene expression activation and energy production are induced in the early stages of the disease. On the contrary, synthesis of these compounds is inhibited whereas its transport is up-regulated later in the process, which correlates with the induction of virulence genes and the metabolism of nitrogen and carboxylic acids. We also found that activation of plant defense mechanisms affects bacterial polyamine synthesis to some extent, which could reduce bacterial cell fitness in the plant environment. Furthermore, data suggest that a proper bacterial response to oxidative conditions requires a decrease in polyamine production. The implications of these findings are discussed.